Efficacy of Antiviral Treatment in Hepatitis C Virus (HCV)-Driven Monoclonal Gammopathies Including Myeloma - Rodríguez-García, Alba; Linares, María; Morales, María Luz; Allain-Maillet, Sophie; Mennesson, Nicolas; Sanchez, Ricardo; Alonso, Rafael; Leivas, Alejandra; Pérez-Rivilla, Alfredo; Bigot-Corbel, Edith; Hermouet, Sylvie; Martínez-López, Joaquín (Frontiers in Immunology, 2022)
Multiple myeloma (MM) remains an incurable plasma cell malignancy. While its origin is enigmatic, an association with infectious pathogens including hepatitis C virus (HCV) has been suggested. Here we report nine patients with monoclonal gammopathy of undetermined significance (MGUS) or MM with previous HCV infection, six of whom received antiviral treatment. We studied the evolution of the gammopathy disease, according to anti-HCV treatment and antigen specificity of purified monoclonal immunoglobulin, determined using the INNO-LIA HCV Score, dot-blot assays, and a multiplex infectious-antigen microarray. The monoclonal immunoglobulin from 6/9 patients reacted against HCV. Four of these patients received antiviral treatment and had a better evolution than untreated patients. Following antiviral treatment, one patient with MM in third relapse achieved complete remission with minimal residual disease negativity. For two patients who did not receive antiviral treatment, disease progressed. For the two patients whose monoclonal immunoglobulin did not react against HCV, antiviral treatment was not effective for MGUS or MM disease. Our results suggest a causal relationship between HCV infection and MGUS and MM progression. When HCV was eliminated, chronic antigen-stimulation disappeared, allowing control of clonal plasma cells. This opens new possibilities of treatment for MGUS and myeloma.